(untitled) (PerCursos, 2024)
The publication of this interview, with the writer Lia Vieira, was carried out collectively, based on a collaboration between the black collective Sarau Vozes Negras (SVN) and “Corsciência: Grupo de pesquisa de tradução e contação de histórias com cor-agem”. This interview consists of the transcription of one of the episodes of the program “conVersos: papos afroliterários”, scripted and performed by members Feibriss Ametista Henrique Meneghelli Cassilhas, Jeff Jeffa Moreira Santana and Nana Martins, broadcast in Lives format and saved in Reels format by the account from SVN on Instagram, @vozesnegras, and posted on our channel on the YouTube platform, Acervo do Sarau Vozes Negras. The transcription of the program was carried out by Corsciência members, Feibriss Ametista Henrique Meneghelli Cassilhas (coordinator) and Jacqueline Augusta Leite de Lima.